Utilizing 2‐phenylpropanal as coupling partner for C‐S bond formation via sequential thioarylation and decarbonylation process: A novel strategy for the synthesis of aryl alkyl sulfides. (8th September 2019) - Shaikhi Shahidzadeh, Elham; Nowrouzi, Najmeh; Abbasi, Mohammad
Abstract : In this study, first direct access to aryl alkyl sulfides employing 2‐phenylpropanal as coupling partner is reported. Diaryl disulfides react with this aldehyde in the presence of morpholine and produce the corresponding sulfide products in high yields. In another part, disulfides are in situ generated in the reaction mixture from aryl halides/CuI/Cyanodithioformate and coupled with 2‐phenylpropanal to access aryl alkyl sulfides. Abstract : Direct access to aryl alkyl sulfides employing 2‐phenylpropanal as coupling partner.